1993
DOI: 10.2169/internalmedicine.32.50
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Amyloidosis in a Patient with Adult Onset Still's Disease.

Abstract: A 39-year-old womanpresented clinical features of adult onset Still's disease. Seven years after the onset, she developed renal insufficiency and biopsy studies revealed amyloid deposits involving amyloid A protein, P component, k chain and k chain in the kidney and rectum. She died in 1992, primarily due to cardiac failure associated with amyloidosis, indicating that amyloidosis should be considered one of the fatal complications in adult onset Still's disease with a long history. (Internal Medicine 32: 50-52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…In contrast to PAH, amyloid A amyloidosis is becoming extremely rare owing to the improved ability of AoSD treatments to control inflammation [150][151][152][153][154][155] . Amyloidosis might occur in patients with refractory disease or in patients who do not have access to adequate treatments for long periods of time.…”
Section: Amyloidosismentioning
confidence: 99%
“…In contrast to PAH, amyloid A amyloidosis is becoming extremely rare owing to the improved ability of AoSD treatments to control inflammation [150][151][152][153][154][155] . Amyloidosis might occur in patients with refractory disease or in patients who do not have access to adequate treatments for long periods of time.…”
Section: Amyloidosismentioning
confidence: 99%
“…In AAA from any cause, early studies suggested some efficacy of azathioprine [82], methotrexate associated with corticosteroids [83], chlorambucil [84], colchicine [85], and cyclophosphamide [86]. However, others showed only a partial regression of renal disease with chlorambucil, corticosteroids, cyclophosphamide, and colchicine [53,55,57,60,61]. Therefore, despite these initial glimmers of hope, AAA remained until recently a difficult-to-treat complication with a dismal prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-five were used to assess AAA prevalence [1,. Sixteen [12,15,22,32,[53][54][55][56][57][58][59][60][61][62][63][64] were used for the descriptive analysis of patients with AOSD and AAA, including 4 articles selected for the prevalence study and 12 individual case reports.…”
Section: Literature Searchmentioning
confidence: 99%
“…Amyloid A amyloidosis is becoming extremely rare owing to the better ability of AoSD treatments to control inflammation [89][90][91][92][93]. It could be observed in refractory patients or in patients who did not have access to adequate treatments for long periods of time.…”
Section: Exceptional Symptomsmentioning
confidence: 99%
“…Acute renal failure is possible in the context of severe myositis, hepatic insufficiency, or hematological complications [21,74,[102][103][104]. -Secondary amyloid A amyloidosis (AA amyloidosis) is nowadays exceptional and is related to sustained uncontrolled inflammation [89][90][91][92][93].…”
Section: Exceptional Symptomsmentioning
confidence: 99%